Acute Posterior Shoulder Dislocation with Reverse Hill-Sachs Lesion of the Epiphyseal Humeral Head. (25th July 2011) - Patrizio, Luigi; Sabetta, Ettore
Abstract : Posterior dislocation of the shoulder is an unfrequent event that often occurs as a consequence of a direct trauma or epileptic crisis. Frequently the posterior dislocations are misunderstood, so they become chronic lesions. We reported a case of an acute posterior left shoulder dislocation with lesser tuberosity fracture and reverse Hill-Sachs lesions which involved more than 25% of the articular surface of the humeral head, in a 57-old-year man with right hemiparesis. We performed a synthesis of the lesser tuberosity with a screw, and we restored the shape of the humeral head with allograft. We achieved a good result that allows the patient to be able to do his previous activities of daily living.